2020
DOI: 10.1016/j.rmcr.2020.101174
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette or vaping product use associated lung injury, (EVALI) - A diagnosis of exclusion

Abstract: Inhalation of aerosolized products generated by different electronic devices is called vaping. E-cigarettes or Vaping product use Associated Lung Injury (EVALI) outbreak peaked in August–September 2019 and gradually declined. EVALI remains a diagnosis of exclusion which presents as an acute lung injury in the vaping population. Vitamin E acetate and its products are implicated as one of the cytotoxic agents causing airway centered pneumonitis. Lipid laden macrophages are found in samples of BAL fluid but their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…The e-cigarette-induced changes in lipid metabolism of macrophages in mice are particularly interesting because similar lipid-laden macrophages have also been observed in humans who use e-cigarettes, particularly in individuals with e-cigarette-associated pneumonia [ 101 , 102 ]. Similar lipid-laden macrophages have also been detected in the BAL fluid of EVALI patients [ 103 ]. Although such lipid-laden macrophages have also been found in the lung of smokers, in e-cigarette users, these macrophages are associated with inflammatory cytokines such as IL-4 and IL-10, but not with smoking-related cytokines [ 104 ], suggesting that the pathophysiological changes induced by e-cigarettes in macrophages may be different in nature from that afflicted by combustible cigarettes.…”
Section: E-cigarettes and The Immune Responsesupporting
confidence: 52%
“…The e-cigarette-induced changes in lipid metabolism of macrophages in mice are particularly interesting because similar lipid-laden macrophages have also been observed in humans who use e-cigarettes, particularly in individuals with e-cigarette-associated pneumonia [ 101 , 102 ]. Similar lipid-laden macrophages have also been detected in the BAL fluid of EVALI patients [ 103 ]. Although such lipid-laden macrophages have also been found in the lung of smokers, in e-cigarette users, these macrophages are associated with inflammatory cytokines such as IL-4 and IL-10, but not with smoking-related cytokines [ 104 ], suggesting that the pathophysiological changes induced by e-cigarettes in macrophages may be different in nature from that afflicted by combustible cigarettes.…”
Section: E-cigarettes and The Immune Responsesupporting
confidence: 52%
“…The immediate effects of oral or inhaled THC induces bronchodilation both in healthy subjects and those with asthma,220 221 but aerosolized THC or cannabis smoking may also result in an irritation of the airways and bronchoconstriction in some individuals with reactive airway disease 222. Evidence of harm is limited to small case series and case reports 212 223–229. A small clinical trial and several case reports of patients with acute shortness of breath and hemoptysis within hours of cannabis use have been published 230–233.…”
Section: Methodsmentioning
confidence: 99%
“…E-cigarette or vaping product use–associated lung injury is a diagnosis of exclusion 6 in a patient with acute lung injury and e-cigarette or vaping product use before symptom onset 7 . A recent study of the CT scans of patients with EVALI showed 96% had ground-glass opacities, 42% had consolidation, and 29% demonstrated smooth interlobular septal thickening 8 .…”
Section: Discussionmentioning
confidence: 99%